The element of leadership in the validation of a model of quality management for schools (Educação e Pesquisa, 2010)
As a nation achieves higher levels of development, the non-educational organizations gradually incorporate into their tasks elements of leadership, strategic planning, organizational development, and assessments of the quality of their management, applying systematic improvement programs. Such emphasis on the management has also been felt in the realm of educational institutions, with leadership being one of the more recurring factors in the management of these organizations. In this context, the aim of the present article is of revealing the importance of the leadership element in the school communities of Chile, and its relationship with the quality of education. The study has allowed determining the effects of variables associated with school management, chiefly among them the variable of leadership, upon the quality of education. To such end, a structured survey was made with a sample of 870 teachers from public and private education centers. Next, a comprehensive psychometric analysis of the data was carried out through a series of exploratory and confirming analyses that included structural equations. The investigation brings forward the reality of schools as organizations. As time goes by, they are changing into ever more complex systems, in which the leadership exercised at an educational center becomes one of the fundamental variables that determine the success in achieving the objectives proposed by the organization.